Serological responses to SARS-CoV-2 in urban and rural Ghana: Antibody waning and implications for long-term population immunity - George Agyei; Philip El-Duah; Rexford Mawunyo Dumevi; Therese Muzeniek; Sherihane Aryeetey; Brice Armel Nembot Fogang; Jonathan M. Gmanyami; Augustina Angelina Sylverken; Yaw Adu-Sarkodie; Richard Odame Phillips; Michael Owusu; Christian Drosten (PLoS ONE, 2026)
Background Ghana exhibits geographic variation across northern and southern regions alongside differences between urban and rural communities, which may influence SARS-CoV-2 exposure and immune response. This study aimed to assess the differences in seroprevalence, and seroconversion status after exposure to SARS-CoV-2 in selected urban and rural Ghanaian communities. Methods A longitudinal study design was employed. Serum samples (n = 987) were collected during a baseline survey (August 2023–February 2024) with longitudinal follow-up (n = 212) sampling after one year (August 2024-February 2025) among consenting community participants aged ≥10 years selected through household-based sampling in urban and rural settings. Socio-demographic data, clinical symptoms, and vaccination status were collected using structured questionnaires. Serum samples were inactivated and tested with semi-quantitative Anti-SARS-CoV-2 IgG ELISA assays targeting spike (S) and nucleocapsid (N) proteins. Presence of SARS-CoV-2 neutralizing antibodies in serum was determined by a surrogate virus neutralization assay. Results Of 987 participants aged 10–88 years (67.3% female), SARS-CoV-2 seroprevalence was comparable between urban (47.4%) and rural (47.7%) areas. Among the 212 participants followed longitudinally, 50.9% (108 participants) had both infection or vaccine-induced anti-spike and infection-induced anti-nucleocapsid antibodies after one year, indicating sustained immune responses from prior exposure or vaccination. There was a significant increase in paired spike and nucleocapsid antibody responses between baseline and follow-up (McNemar’s test, χ²(1) = 104.00, p < 0.0001), reflecting ongoing immune boosting despite evidence of antibody waning. Neutralizing antibodies, were detected in 147/148 (99.3%) individuals at timepoint-1 and in all 12 (100%) selected individuals for follow-up at timepoint-2, demonstrating robust functional immunity. Conclusion This study demonstrates widespread serological evidence of prior SARS-CoV-2 exposure and vaccine-induced immunity in both urban and rural Ghana. Functional neutralising antibodies were detected in a longitudinal subset, suggesting persistence of antibody-mediated protection in some individuals. Larger longitudinal studies with repeated functional immune assessments are needed to better define durable protection in West African settings.